A comparison of marine radionuclide dispersion models for the Baltic Sea in the frame of IAEA MODARIA program. (January 2015) - Periáñez, R.; Bezhenar, R.; Iosjpe, M.; Maderich, V.; Nies, H.; Osvath, I.; Outola, I.; de With, G.
Abstract: Four radionuclide dispersion models have been applied to simulate the transport and distribution of 137 Cs fallout from Chernobyl accident in the Baltic Sea. Models correspond to two categories: box models and hydrodynamic models which solve water circulation and then an advection/diffusion equation. In all cases, interactions of dissolved radionuclides with suspended matter and bed sediments are included. Model results have been compared with extensive field data obtained from HELCOM database. Inventories in the water column and seabed, as well as 137 Cs concentrations along 5 years in water and sediments of several sub-basins of the Baltic, have been used for model comparisons. Values predicted by the models for the target magnitudes are very similar and close to experimental values. Results suggest that some processes are not very relevant for radionuclide transport within the Baltic Sea, for instance the roles of the ice cover and, surprisingly, water stratification. Also, results confirm previous findings concerning multi-model applications. Highlights: Box and hydrodynamic models applied to Chernobyl 137Cs dispersion in the Baltic Sea. Calculated concentrations in water and sediments compared with HELCOM database measurements. Good agreement found between models and measurements. Some processes surprisingly not relevant for radionuclide transport (stratification, ice). Previous findings on multi-model applications have been confirmed.